2020
DOI: 10.25124/jaf.v4i2.3294
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Accounting Information Use and Internal Characteristics of Entrepreneurs Toward Productivity of Small and Medium Enterprises in Banyumas Regency

Abstract: This study aims to examines the effect of the use of accounting information and internal characteristics of entrepreneurs including accounting training, business scale and educational level toward productivity of SME’s. The use of accounting information and internal characteristics of entrepreneurs is measured by Likert scale and scale score. The sample of 94 respondents of SME entrepreneurs is selected from the population of all SME entrepreneurs in Banyumas Regency, using the quota sampling method. Analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…After reviewing the selection process for SINTA-4 indexed journals and articles according to the established criteria, 21 journals (4.8% of 441 journals) containing 129 MAR articles (6% of 2300 articles) in 2011-2022 were obtained. Although the names of 21 journals that fit these criteria are in Indonesian, five articles identified were published in English (Aulia & Setyorini, 2021;Bawono et al, 2020;Lawita & Samsiah, 2018;Nurleli et al, 2022;Purba & Sari, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the selection process for SINTA-4 indexed journals and articles according to the established criteria, 21 journals (4.8% of 441 journals) containing 129 MAR articles (6% of 2300 articles) in 2011-2022 were obtained. Although the names of 21 journals that fit these criteria are in Indonesian, five articles identified were published in English (Aulia & Setyorini, 2021;Bawono et al, 2020;Lawita & Samsiah, 2018;Nurleli et al, 2022;Purba & Sari, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…A study in a developing country, Ghana, found that owners'/managers' educational level does not influence SMEs' performance (Amarteifio & Agbeblewu, 2017). Some argue that Higher education of owners/managers in finance influences SMEs' performance, sustainability, and growth (Bawono et al, 2020;Eniola & Entebang, 2016). A higher education level of owners/managers improves the transfer of knowledge within SMEs and influences a firm's performance (Kankisingi & Dhliwayo, 2016).…”
Section: Education Levelmentioning
confidence: 99%
“…The MSMEs also responded to the survey after being contacted via telephone or email or in person. The MSMEs were chosen from the population through quota sampling technique (Nonprobability sampling technique) (Sunday et al, 2015;Bawono et al, 2020;Samsuri et al, 2021).The final sample consisted of 400 MSMEs (i.e., 80 samples from each state). The distribution of the data was verified by plotting Q-Q plot and two statistical tests of normality namely Kolmogorov-Smirnov and Shapiro-Wilk which confirms the normal distribution of data.…”
Section: Survey Instrument and Sampling Designmentioning
confidence: 99%